Stratification of the Low-Latitude and Near-Equatorial F2 Layer, Topside Ionization Ledge, and F3 Layer: What We Know about This? A Review - M. V. Klimenko; B. Zhao; A. T. Karpachev; V. V. Klimenko (International Journal of Geophysics)
A large number of researches have been devoted to the formation of additional layers in the F region of the equatorial ionosphere, first of which has been published in 1940s. Originally the occurrence of such layer was named “stratification of equatorial F2 layer.” The additional layer was later named as the F3 layer. The theoretical researches have shown that the F3 layer is formed by zonal component of electric field with assistance of meridional component of thermospheric wind and field-aligned plasma diffusion. The physical mechanism of the F3 layer formation is clearly formulated for the morning-noon period, although the F3 layer is also observed at other hours. This paper presents a brief review into the history of the additional layer researches, describes the current progress of these researches, and identifies the most important problems in this field of the ionospheric physics.